An Exploration of EFL Students' Perceptions of AI-Integration in the Learning Process - Syafrayani, Putri Rizki; Ayunda, Riska; Molina, Merry Luz; Tambunan, Anna Riana Suryanti; Murni, Sri Minda (English Education Department at FKIP Nommensen University, 2025)
This study explores EFL students’ perceptions of artificial intelligence (AI) integration in language learning, utilizing Kahneman’s Dual Process Theory (2011) to examine intuitive (System 1) and reflective (System 2) cognitive responses. The study aims to understand how junior EFL learners engage with AI tools, and to explore the perceived benefits and challenges of AI-assisted learning. A qualitative research approach was employed, involving 14 students from a Junior-Teenager Conversation class in Medan, selected through convenience sampling. Data were collected using a two-part questionnaire: the first part consisted of multiple-choice items to assess instinctive, emotional reactions, while the second part included open-ended questions to elicit analytical and evaluative responses. Data were gathered during regular classroom sessions and analyzed thematically using Braun and Clarke’s (2006) five-phase framework. The findings revealed that 71.4% of students found AI tools “interesting,” while 7.1% felt “optimistic” and 21.4% “amazed.” Key benefits included AI’s user-friendly interface (42.9%) and well-explained responses (35.7%), while concerns included reduced learning effort (57.1%) and potential academic dishonesty (35.7%). The study highlights the dual impact of AI enhancing personalization and engagement, while presenting ethical and pedagogical challenges. It recommends balanced integration of AI in EFL learning and further research into its long-term effects.